Transfer of heavy metals along the food chain: A review on the pest control performance of insect natural enemies under heavy metal stress - Zhang, Zhe; Wu, Hongfei; Zhang, Aoying; Tan, Mingtao; Yan, Shanchun; Jiang, Dun (Journal of hazardous materials, 2024)
Heavy metal contamination represents a critical global environmental concern. The movement of heavy metals through the food chain inevitably subjects insect natural enemies to heavy metal stress, leading to various adverse effects. This review assesses the risks posed by heavy metal exposure to insect natural enemies, evaluates how such exposure impacts their pest control efficacy, and investigates the mechanisms affecting their fitness. Heavy metals transfer and accumulate from soil to plants, then to herbivorous insects, and ultimately to their natural enemies, impeding growth, development, and reproduction of insect natural enemies. Typically, diminished growth and reproduction directly compromise the pest control efficacy of these natural enemies. Nonetheless, within tolerable limits, increased feeding may occur as these natural enemies strive to meet the energy demands for detoxification, potentially enhancing their pest control capabilities. The production of reactive oxygen species and oxidative damage caused by heavy metals in insect natural enemies, combined with disrupted energy metabolism in host insects, are key factors contributing to the reduced fitness of insect natural enemies. In summary, heavy metal pollution emerges as a significant abiotic factor adversely impacting the pest control performance of these beneficial insects. [Display omitted] •Heavy metals can transfer along the food chain to insect natural enemies.•Heavy metal stress decreases the fitness of insect natural enemies.•Pest control performance of insect natural enemies is effected by heavy metal stress.•Oxidative damage directly reduces fitness of insect enemies under heavy metal stress.•Heavy metal-caused host energy disorder indirectly reduces fitness of insect enemies.